Targetable Kinase-Activating Lesions in Ph-like Acute Lymphoblastic Leukemia - Roberts, Kathryn G; Li, Yongjin; Payne-Turner, Debbie; Harvey, Richard C; Yang, Yung-Li; Pei, Deqing; McCastlain, Kelly; Ding, Li; Lu, Charles; Song, Guangchun; Ma, Jing; Becksfort, Jared; et al. (The New England journal of medicine, 2014)
About 25% of young adults with ALL have Ph-like genotypes, which are associated with poor outcomes with conventional treatment. In this gene-expression study, a substantial fraction of Ph-like ALL cases were found to involve activation of kinases targeted by available agents.